Your product development process demands ongoing improvement - Smith, Preston G.
Preston G. Smith presents a 12-step process for doing what the winners do : make every project a learning process.
Winners at new product development make every project a learning process. Here are 12 steps to reaching that level.
Although managers routinely review their product development projects to ensure that each is achieving its objectives, they seldom review the development process itself to identify and overcome its shortcomings. This article provides a 12-step process for capturing the learning from each project. The first step is selecting a name for the process that is preferably not the popular one, "postmortem." The last and most crucial step is converting the findings from each project into actual changes in the development process. This amounts to giving process change actions the same level of attention that development projects receive. Nine companies provide illustrations of the principles involved, showing that a well-tuned development process is a competitive advantage that repays the investment required to obtain it.
Keywords: Product development